The Importance of Fine Needle Aspiration Cytology and Core Needle Biopsy in The Diagnosis of Palpable Breast Mass in Karbala City - Alshami, Mohammed Ahmed; Aldadah, Safa Ahmed; Hasan, Jehan Sabah; Ali, Raghad Hussein (Scientific Journal of Medical Research, 2020)
Background: Palpable breast lesion is commonly found in females in different age groups. A variety of diagnostic approaches (as adjunct to triple assessment) have been used to elicit the real pathology before deciding the final management. For many years Fine Needle Aspiration (FNAC) was the most popular way to establish the cytological diagnosis. Core Needle Biopsy (CNB) was then introduced to get more information about histopathological type. Objectives: Aim of the study is to compare between FNAC and CNB regarding sensitivity and specificity and the possibility of replacing FNAC by CNB. Methods: This study involves one hundred and eleven female patients complaining of palpable breast mass for the period extending from August 2017 to December 2018 in our breast clinic at Al-Hussein teaching medical city Karbala / Iraq. Fine needle aspiration was done followed by non-ultrasound guided true cut biopsy at the same session followed by Proper surgical treatment. Histopathological and cytological study was done to all samples. The results were analyzed by SPSS program. Results: The age ranges from 17 to 80 years. Mean age of 47.8 years and standard deviation of 12.15. 61% of the patients are in the age group of 40 to 59 years. Seventy-seven patients (69.4%) were discovered to carry malignant lesions while 34 patients (30.6%) had benign conditions. 94.8% of the malignant lesions were ductal carcinoma and 32.4% of the benign lesions were fibroadenomas. FNAC Sensitivity and Specificity; Positive Predictive and Negative Predictive values are 84.4%, 97.1%, 98.5% and 73.3% respectively. CNB Sensitivity and Specificity; Positive Predictive and Negative Predictive values are 94.8%, 100%, 100% and 89.5% respectively Conclusion: CNB is more sensitive and more specific than FNAC which cannot be replaced completely by CNB. Both are complementary to each other. The introduction of Ultrasound guidance method for both FNAC and CNB is better to be accomplished to avoid missing malignancies.